Botswana branding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
It was two years of hard work, but in Q3 (third quarter) of 2002, Botswana s Ministry of Agriculture confirmed that 600,000 cattle in the country had been branded under the Livestock Identification and Trace-Back System (LITS). LITS branding...